The Contributions of BAZNAS to Mitigate the Covid-19 Pandemic Impacts in Indonesia - Isna Fauziah Biljannah (SMART Insight, 2022)
This study tries to analyze the contribution of BAZNAS through Zakat, Infaq, Alms, and Waqf (ZISWAF) funds to mitigate the impact of COVID-19 in the fields of economy, education, social humanity, health, and da'wah in Indonesia and to know which aspect has a bigger role than the five aspects studied. This study uses a qualitative and quantitative approach (mixed method). The data collection technique was carried out through in-depth interviews with experts consisting of academics, practitioners, scholars, and regulators. The data analysis technique uses Analytical Network Process (ANP) with Super Decision 2.10 software. The results of this study are that of the five aspects studied, 1) social & humanitarian criteria have the highest weight and become a priority for BAZNAS's contribution to mitigating the risk of the impact of COVID-19 in Indonesia. Another order of priority: 2) health; 3) da’wah; 4) education; 5) economy which is the last priority for BAZNAS's contribution. The potential implication of this research is to provide alternative strategies for BAZNAS in making some decisions.